2017
DOI: 10.1016/j.prevetmed.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of small-scale livestock keepers for national biosecurity—The pig case

Abstract: Small-scale keepers are less likely to engage with production organisations and may therefore be less aware of legislation, rules and biosecurity practices which are implemented in the livestock sector. Their role in the transmission of endemic and exotic diseases is not well studied, but is believed to be important. The authors use small-scale pig keepers in Scotland as an example of how important small-scale livestock keepers might be for national biosecurity. In Scotland more than two thirds of pig producer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…Similarly, Gillespie et al (2015) reported that small-scale pig holders in England owned poultry (74.5%) and sheep (48.4%) in addition to dogs and cats (79.3%) [18]. A concern with mixed farms (i.e., with different animal species) is that they may be more prone to disease transmission and animal contacts, and therefore pose a unique risk to introduction and spread of endemic and exotic diseases [18,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Gillespie et al (2015) reported that small-scale pig holders in England owned poultry (74.5%) and sheep (48.4%) in addition to dogs and cats (79.3%) [18]. A concern with mixed farms (i.e., with different animal species) is that they may be more prone to disease transmission and animal contacts, and therefore pose a unique risk to introduction and spread of endemic and exotic diseases [18,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, about one-third considered their animals as pets, similar to urban livestock owners surveyed in 48 cities [20]. The small-scale and backyard owners keep animals to ensure a better source of food, to be assured where their food comes from and how is it produced [14,20,28]. Moreover, they perceived their eggs and meat were higher quality, more nutritious, safer to consume and tasted better than those raised in commercial settings, and also perceived that their chickens were healthier and experienced better welfare [14,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It means that, changes in educations and keeping systems had no contribution on experiences. Experiences of a farmers will then be resulted from informal education and how farmers tethered their farming business (Fynbo and Jensen, 2018;Boogaard et al, 2011;Lassen et al, 2006;Correia-Gomes et al, 2017).…”
Section: On-farm Social Assets Overviewmentioning
confidence: 99%